SISTEM INFORMASI PENJUALAN BERBASIS WEB MENGGUNAKAN METODE WATERFALL PADA TOKO FAMILY CELL - Pratama Siregar, Hari Nanda; Suherman, Suherman; Hendry, Hendry (Indexia, 2025)
Sales information systems are an important component in supporting the efficiency and effectiveness of business operations, especially in the retail sector such as Toko Family Cell. The recording process that is still done manually causes various obstacles, such as inaccuracy in sales reports, errors in stock recording, and slow decision-making processes. This study aims to design and develop a web-based sales information system using the Waterfall method consisting of five stages: needs analysis, design, implementation, testing, and maintenance. The system developed only has one user level, namely admin, in accordance with the needs of the store which is only managed by the owner and one employee. The main features in this system include login, product data management (card and voucher stock), sales transactions and balance top-ups, and report printing. The system has been tested using the Lighthouse method which showed positive results. In addition, a simple embedding algorithm is applied to represent product data in numeric form to support the development of product recommendation features in the future. The final results show that this system is able to increase the speed, accuracy, and ease of transaction processes and sales data management at Toko Family Cell.